Harmonizing the healing of hand trauma in a piano teacher: a case report on pain management in Ireland and utilizing butterfly ultrasound for a brachial plexus nerve block (UCC Student Medical Journal, 2024)
Background:This case report outlined a specialized surgical technique designed for the restoration of intricate hand functionality after a complex hand injury. It also highlighted the use of Butterfly iQ+ and its integration with iOS devices for teaching ultrasound techniques during the administration of a brachial plexus nerve block. Finally, concerns regarding pain management protocols in Ireland were raised. Case Details:A 58-year-old piano teacher presented with a significant hand trauma. The restoration of intricate hand functionality essential for her profession as a piano teacher was a central concern. Her treatment included surgical exploration and wire fixation of the fractures. The application of Butterfly Ultrasound played an interesting role as an educational tool in anesthetic administration. Discussion:The case presented significant challenges in postoperative rehabilitation, necessitating an adjustment to a more conservative approach due to the patient's high pain levels. This adjustment highlighted gaps in pain management and anesthetic care, especially during the transition from hospital to home care, revealing broader issues in Ireland's rehabilitation systems. The postoperative prescription of Oxycontin was inconsistent with established guidelines, pointing to a need for improved integration between primary and tertiary care. Conclusion:This case underscored the importance of patient-specific, adaptable management strategies in trauma recovery. It showcased the potential role of Butterfly Ultrasound in clinical settings for anesthetic guidance and educational purposes. Finally, the report further prompted a broader dialogue on the improvement of pain management practices, particularly concerning the rise in opioid prescriptions in Ireland.
Keywords: hand; trauma; POCUS; butterfly-ultrasound